PENGARUH KINERJA KEUANGAN PERUSAHAAN TERHADAP TINGKAT PENGUNGKAPAN CSR PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR PADA BEI TAHUN PERIODE 2020-2022 - Wartama, I Nyoman Widnyana; Dewi, Ni Luh Yulyana; Latupeirissa, Jonathan Jacob Paul (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to determine the influence of the financial performance of property and real estate sector companies as measured using the Return on Equity (ROE), Net Profit Margin (NPM), and Debt to Equity Ratio (DER) proxies on the level of CSR disclosure in 2020-2022. The research sample consisted of 12 companies selected using the purposive sampling method. Data was obtained via the official Indonesia Stock Exchange (IDX) website and analyzed using multiple linear regression analysis techniques. The research results show that ROE has no effect on the level of CSR disclosure, meaning that companies with a high level of profitability tend not to disclose Corporate Social Responsibility (CSR). NPM has no effect on CSR disclosure, meaning that high or low profits obtained by the company do not influence the company's decision to disclose CSR. Meanwhile, DER influences CSR disclosure, meaning that the size of a company's leverage ratio can influence the amount of Corporate Social Responsibility disclosure made by the company.